Analysis of Anxiety Scale and Related Elements in Endodontic Patients - Akhavan, Hengameh; Mehrvarzfar, Payman; Sheikholeslami, Mahshid; Dibaj, Masomeh; Eslami, Shahrooz (Iranian Endodontic Journal, 2008)
INTRODUCTION: Anxiety of patients is one of the problems in dentistry which are considered in recent years, and it prevents them from having a treatment out of stress. This study was conducted to specify anxiety prevalence and related elements among endodontic patients. MATERIALS AND METHODS: The study was conducted on 150 patients referred to Endodontic department of dental school of Islamic Azad University, using a cross sectional descriptive method in 2006. Using background characteristics, the patients were classified as a matter of age, sex, education and related factors such as previous dental visit, unfavorable experience in dental office, and the most prevalent cause of referring to dentist. In this regard, Dental Fear Survey (DFS), questionnaire was used and patients were divided in three groups of anxiety level. The results were analyzed using Chi-square and Fisher exact tests. RESULTS: The findings showed highest anxiety scales among dental office referents were statistically significant for age group of 20-30, women, and under diploma education (P<0.05). CONCLUSION: Improving the knowledge about causes of anxiety and its preventive methods are suggested to dentists. They should also provide treatments without annoyance and trauma.